Hiérarchies - Pierre COTTE (E-REA)
In this paper a hierarchy is defined as a relation between a head and a dependency. The paper studies some of the semantic hierarchies that occur in sentences, focussing on their syntactic realization and interactions. It is also concerned with the relation between sentence meaning and interpretation.The study is based on the analysis of the opening sentence of Sanctuary by William Faulkner.